APPARATUS FOR LOAD TEST - CHOI, YOUNG KUN; LEE, DONG CHEON; LEE, JEONG MIN (2015)
A load test apparatus is provided. The load test apparatus for testing the load of a subject fixed in a ceiling structure according to one embodiment of the present invention includes a jig which is fixed to the subject to protrude to both sides of the subject, a plurality of hydraulic cylinders which are located between the ceiling structure and both upper ends of the jig which protrude, and a hydraulic pump which extends the hydraulic cylinders by supplying hydraulic pressure to the hydraulic cylinders. 하중 테스트 장치가 제공된다. 본 발명의 일 실시예에 따른 하중 테스트 장치는, 천장 구조물에 고정된 피검사체의 하중을 테스트하기 위한 하중 테스트 장치에 있어서, 상기 피검사체의 양측으로 돌출되도록 상기 피검사체에 고정되는 지그; 상기 지그의 돌출된 양측 상단과 상기 천장 구조물 사이에 위치하는 복수의 유압 실린더; 및 상기 복수의 유압 실린더에 유압을 공급하여 상기 복수의 유압 실린더를 신장시키는 유압 펌프를 포함한다.